Autorzy:Janowicz Jerzy
Wydawnictwo:Nowa Era
Rok wydania:2015
Rozwiąż równanie. 4.5 gwiazdek na podstawie 6 opinii

`a)\ 6-[2(x-5)+9]=1/3x+7` 

`\ \ \ 6-[2x-10+9]=1/3x+7` 

`\ \ \ 6-(2x-1)=1/3x+7` 

`\ \ \ 6-2x+1=1/3x+7` 

`\ \ \ 7-2x=1/3x+7\ \ \ |-7` 

`\ \ \ -2x=1/3x\ \ \ |+2x` 

`\ \ \ 2 1/3x=0\ \ \ |:2 1/3` 

`\ \ \ x=0` 

 

 

`b)\ 9,5-{8,5-[7,5-(6,5-4,5x)]}=-2,5` 

`\ \ \ 9,5-{8,5-[7,5-6,5+4,5x]}=-2,5` 

`\ \ \ 9,5-{8,5-[1+4,5x]}=-2,5` 

`\ \ \ 9,5-{8,5-1-4,5x}=-2,5` 

`\ \ \ 9,5-{7,5-4,5x}=-2,5` 

`\ \ \ 9,5-7,5+4,5x=-2,5` 

`\ \ \ 2+4,5x=-2,5\ \ \ |-2` 

`\ \ \ 4,5x=-4,5\ \ \ |:4,5` 

`\ \ \ x=-1` 

 

`c)\ (2x+3)/5+(7x)/10=x+4\ \ \ |*10` 

`\ \ \ 2(2x+3)+7x=10x+40` 

`\ \ \ 4x+6+7x=10x+40` 

`\ \ \ 11x+6=10x+40\ \ \ |-10x` 

`\ \ \ x+6=40\ \ \ |-6` 

`\ \ \ x=34` 

 

`d)\ (1/2x+1)/3-(1/3x+1)/2=1/3x\ \ \ |*6` 

`\ \ \ 2(1/2x+1)-3(1/3x+1)=2x` 

`\ \ \ x+2-x-3=2x` 

`\ \ \ 2x-1=2x\ \ \ |-2x` 

`\ \ \ -1=0` 

równanie jest sprzeczne

 

`e)\ ((x+1)/2+(x-1)/3)/6=1\ \ \ |*6` 

`\ \ \ (x+1)/2+(x-1)/3=6\ \ \ |*6` 

`\ \ \ 3(x+1)+2(x-1)=36` 

`\ \ \ 3x+3+2x-2=36` 

`\ \ \ 5x+1=36\ \ \ |-1` 

`\ \ \ 5x=35\ \ \ |:5` 

`\ \ \ x=7`